Kalibrasi Jangka Sorong Jam Ukur (Dial Calliper) Dengan Menggunakan Metode Standar JIS B 7507 - 1993 Di Laboratorium Pengukuran Teknik Mesin Universitas Riau - Zulfebri Zulfebri; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The calibration of dial calliper is the form of activity to determine the truth of the conventional value by using measuring ruler with the measuring clock as the substitute of a nonius scale. The degree of accuracy from a dial inching ruler is the same as the nonius inching bar, 0.10 mm, 0.05 mm or 0.02 mm. On the dial inching bar with the accuracy of 0,10 mm by using the standard JIS B 7507-1993 method. As a result of analysis, the uncertainty value of the measuring instrument from dial caliper I at a rate of trust 95% with a coverage factor of k = 2 is U95 = ± 9.50 . The uncertainty value of the dial caliper II at a rate of trust 95% with the coverage factor k = 2 is U95 = ±9,50 . The uncertainty value of the dial caliper III at a rate of trust 95% with the coverage factor k = 2 is U95 = ±9,50 . Measurement error / deviation measuring clock caliper (dial calliper) I and II with the measuring block measuring 150 mm is 0.00007 mm. While the clock measuring caliper (dial calliper) III with the measuring block measuring 150 mm is -0.04993 mm. Based on the table errors that allowed JIS B 7507-1993 is ± 0.07 mm so caliper measuring clock (dial calliper) I, II and III are still within the allowed tolerance limit mistakes and still feasible to be used.Keywords:Calibration, Calliper, Dial Calliper,Standard JIS B 7507-1993